Estimation and prediction of local strain-induced martensitic transformation - Tomita, Y.; Shibutani, Y. (Archives of Mechanics, 1999)
Uniaxial tension tests were performed under constant strain rate and different environmental temperatures from 77 K to 373 K to identify the concrete form of the constitutive equation for TRIP steels. Subsequently, a new experimental procedure based on microhardness testing which provides local information regarding the transformation has been proposed. To elucidate the dependence of the martensitic transformation on the nonuniform deformation and consequently, to validate the proposed constitutive equation, the volume fraction of the martensite phase is predicted and measured by using computational simulation and experimental procedures, respectively, for the uniaxial tension of the bars with a ringed notch. Good correspondence between the local volume fraction of the martensite phase around the notch obtained by both methods verifies the validity of the proposed constitutive equation for the nonuniform deformation behavior. It has been farther clarified that the development of the martensitic phase may relieve the strain localization around the notch tip and subsequently, will increase the energy absorption which is accompanied by an improvement in the toughness.